Physical activity and gestational weight gain: a systematic review of observational studies - Virginie Hamann; Philippe Deruelle; Christophe Enaux; Séverine Deguen; Wahida Kihal-Talantikite (BMC, 2022)
Abstract Background Now that excessive weight gain during pregnancy is recognized as leading to complications during pregnancy that affect foetal growth, limiting weight gain during pregnancy has become a public health concern. Our aim was to perform a systematic review to assess whether observational studies reported associations between Physical Activity (PA) and Gestational Weight Gain (GWG). We were particularly interested in whether insufficient PA might be associated with high GWG. Methods Using Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, we searched the MEDLINE ® databases for articles published up to February 2020 concerning case-control, cohort, and ecological studies assessing the association between PA during pregnancy and the risk of excessive and/or inadequate GWG. Results 21 observational studies on the PA of pregnant women were screened. 11 of these focused on excessive GWG, and of these a majority tend to show a significant association between various aspects of PA and excessive GWG. However, the results were more mitigated when it came to rate of GWG: three studies found that neither meeting PA recommendations nor high levels of total PA nor time spent in moderate vigorous physical activity (MVPA) or engaged in sedentary behaviour were associated with weekly GWG, while two others suggested that pregnant women not meeting PA guidelines in late pregnancy did have a higher rate of GWG. Of the seven studies investigating total GWG, only one found no association with PA. All studies suggested an inverse association between PA and total GWG - yet not all studies are statistically significant. Conclusion Despite the small number of observational studies selected for our research, our findings support the main international findings, suggesting that active pregnant women gained less weight than inactive women; a lack of PA may therefore contribute to excessive GWG. The limitations of this body of evidence impede the formulation of firm conclusions. Further studies focusing clearly on the general PA assessment classification scheme are called for, to address limitations capable of affecting the strength of association.